Hubungan Prokrastinasi dengan Stres pada Mahasisw Tingkat Akhir yang Sedang Menyusun Skripsi di STIKes Santa Elisabeth Medan Tahun 2021 - Pomarida Simbolon; Maria Maria; Fryska Yohana (LPPM STIKes Indah Medan, 2022)
Students can never stay away from pressure. Stress is an unavoidable condition throughout everyday life and everyone has different feelings of anxiety. Duringgthe time of completing the thesis, studentsparenfacedtwithlvariousnobstacles, requests, anddpressures. Thissis what causesastudents toipreferitoiprocrastinateior procrastinate and it can be seen that student stress is influenced by the procrastination of the student. This research method uses an in-depth exploration configuration usingiaicrossisectionalimethodology. Theiexample inithisireview wasi62irespondents withltheitesting system, specifically basic arbitrary examining. Thei p-valuei ofi 0.001i (p<0.05) indicates that thereiisiairelationshipibetween indecision andistudent stress who compose a student proposal for the Nursing Study Program ofnSTIKes Santa ElisabethmMedan 2021. The expectednthatnstudents can motivate themselves in working on their thesis and manage time so they don't experience problems. stress and no procrastination occurs.